Psychological interventions on a specialist Early Intervention Inpatient Unit: An opportunity to engage?. Issue 6 (29th June 2017) - Reynolds, Nicola; Desai, Roopal; Zhou, Zheng; Fornells‐Ambrojo, Miriam; Garden, Paul
Abstract : Background: This study explored engagement with psychology on a specialist early intervention psychosis inpatient unit, with a focus on whether demographics or admission factors impacted on engagement. Method: This was a retrospective cohort study using data extracted from patient notes for all service users who were admitted to an Early Intervention ward during a specified 6‐month period. One hundred and one records were identified. Results: Sixty‐eight (67.3%) of the service users engaged in psychological therapy, 45.6% (n = 47) attended psychology groups and 58.4% (n = 59) engaged in individual psychology sessions. Service users admitted to the ward voluntarily were more likely to engage in individual psychology sessions in comparison to those admitted under section of the mental health act ( β = −0.270, P < .005). Length of admission predicted engagement with groups ( β = 0.38, P < .001) and individual psychology sessions ( β = 0.408, P < .001). Ethnicity, gender and number of admissions did not predict engagement in psychology. Conclusions: Psychological interventions are acceptable on a specialist early intervention psychosis inpatient ward and offer an opportunity to engage service users. Engagement was not predicted by demographic factors typically seen in community settings. Implications arising from these differences are discussed.